X-ray reflectivity measurements of liquid/solid interfaces under high hydrostatic pressure conditions - Wirkert, Florian J (Journal of synchrotron radiation, 2014)
A high-pressure cell for in situ X-ray reflectivity measurements of liquid/solid interfaces at hydrostatic pressures up to 500 MPa (5 kbar), a pressure regime that is particularly important for the study of protein unfolding, is presented. The original set-up of this hydrostatic high-pressure cell is discussed and its unique properties are demonstrated by the investigation of pressure-induced adsorption of the protein lysozyme onto hydrophobic silicon wafers. The presented results emphasize the enormous potential of X-ray reflectivity studies under high hydrostatic pressure conditions for the in situ investigation of adsorption phenomena in biological systems